PENGEMBANGAN E-MODUL PEMBELAJARAN KESEHATAN DAN KESELAMATAN KERJA DI SMK PENERBANGAN AAG ADISUCIPTO - Arqi Luhur Budi Leksono; Rabiman Rabiman; Samsul Hadi (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2026)
The teaching materials used in learning must be innovative and engaging to help improve students' understanding of occupational health and safety material in vocational high schools. This research aims to produce a Health and Safety e-module that is suitable and effective for use in learning activities. This research uses the research and development method with the 4D model. The research subjects are 16 students from class X TKR at SMK Penerbangan AAG Adisucipto for the 2024/2025 academic year. This research produced an Occupational Health and Safety e-module with A4 paper size specifications, equipped with hyperlink, video, summative and formative evaluation questions. The e-module can be accessed using the Heyzine flipbook website. The results of the material expert assessment obtained a score of 75% and the media expert 92.5%, both of which fall into the very feasible category. Student responses indicate that the e-module is in the very feasible category with a score of 87.8%. In conclusion, the generated Health and Safety e-module is very suitable for teaching basic automotive work subjects to 10th-grade Light Vehicle Engineering students. Therefore, this e-module can be used as a reference to support Health and Safety learning activities.